-8r=-5r-6

Simple and best practice solution for -8r=-5r-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8r=-5r-6 equation:



-8r=-5r-6
We move all terms to the left:
-8r-(-5r-6)=0
We get rid of parentheses
-8r+5r+6=0
We add all the numbers together, and all the variables
-3r+6=0
We move all terms containing r to the left, all other terms to the right
-3r=-6
r=-6/-3
r=+2

See similar equations:

| 3(x+2)+5(x-7)=43 | | -3p-5=-8p-10 | | 3(x+2)=43 | | 68x+88=0 | | -4=4+s | | 1/4p=11 | | -5c-3=-4c | | -6n=66 | | (7x-5)/(3x+2)=9 | | -3d-5=2d | | 5s-2=4s | | -4=4+y | | 14+2x=5x | | -4g=10g-5g | | 0=-4(d-18)+-8 | | 11y-4y+3y+2=12 | | (4x-1)/5=(2x+3)/2 | | t^2(t^2-4)=3t^2-5 | | 3h-2h=2 | | 18b-17b=12 | | (x-2)^2+4=0 | | (6x+10)=7(x–2) | | 5x-25=3(x-7) | | 1-2/3c=9/5-1/5c+5/2 | | 20+x÷3=25 | | 12.3x–18=3(–6+4.1x) | | 9x-4(x-8)=2(x-5)+9 | | 4v=-64 | | (-)24=6v | | 12p+-18p=6 | | 15c+3c-16c=14 | | -13=k/12 |

Equations solver categories